JobCats solving cryptarithmetic puzzle using CSO algorithm - Catalan, Ryan M. (2011)
Job Shop Scheduling Problem (JSSP) is a difficult scheduling problem that has no easy way of getting the optimal value. This problem is well-studied because of its various real-world applications especially in the field manufacturing and service industries since JSSP tends to improve some measures of performance especially the maximum completion time (makespan) that is necessary in businesses. JSSP is among the hardest combinational optimization problems and is classified as an NP-hard problem that is why a lot of optimization algorithms were used to solve JSSP and some have promising results. Inthis paper another optimization algorithm based on the behavior of cats, the Cat Swarm Optimization of CSO algorithm was used to solve JSSP. Experiment results show that CSO was able to find and solve for the optimal value for every JSSP instance used in this paper. These results indicate that CSO is a feasible algorithm in soving Job Scheduling Problems.